WEBINAR UPAYA HILIRISASI PRODUK KOSMETIKA PADA SISWA SMK FARMASI DI SURABAYA - Dewi Isadiartuti; Widji Soeratri; Noorma Rosita; I Gusti Ayu Adhi Aryapatni; Suko Hardjono; Tristiana Erawati; Herra Studiawan; Maria Lucia Ardhani Dwi Lestari; Virnanda Syafira Hartatiningrum (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
Pharmacy Vocational High School (SMK) students are prepared to work immediately after finishing school. Students receive lessons on the basics of pharmaceutical preparation and entrepreneurship. Cosmetics are a pharmaceutical dosage form widely used by the broader community for personal hygiene, appearance improvement, and health functions. The Minister of Health of the Republic of Indonesia No. 1175/Menkes/Per/VIII/2010 concerning cosmetic production permits provides an opportunity for cosmetic products to be produced with simple technology. During the COVID-19 pandemic, which results in a heavy economic burden for the government and society, there are business opportunities for Pharmacy Vocational School students. Community service aims to increase students' knowledge and insight and encourage students in class XI and XII of the Sekesal Pharmacy Vocational School in Surabaya and Kapasari Pharmacy Vocational School in Surabaya to become entrepreneurs in the cosmetics sector. The implementation method is through a webinar that provides material covering products, formulations, stability, and licensing of cosmetic products. Participants had the opportunity to discuss the material provided, fill out evaluations in the form of pre/post-test and make E-posters about cosmetic products. The evaluation results show an increase in participants' knowledge and insight, and participants are interested in producing cosmetic preparations, which are expected to become new business fields that can improve their welfare. --- Siswa Sekolah Menengah Kejuruan (SMK) Farmasi dipersiapkan untuk segera bekerja setelah menamatkan sekolah. Siswa memperoleh pelajaran tentang dasar-dasar pembuatan sediaan farmasi dan kewirausahaan. Kosmetika merupakan salah satu bentuk sediaan farmasi yang banyak digunakan oleh masyarakat luas untuk tujuan kebersihan diri, peningkatan penampilan, dan memiliki fungsi kesehatan. Permenkes RI No 1175/Menkes/Per/VIII/2010 tentang izin produksi kosmetika memberikan peluang produk kosmetika diproduksi dengan teknologi sederhana.  Dalam  masa pandemi covid 19, yang mengakibatkan beban ekonomi berat bagi pemerintah dan masyarakat, terdapat peluang usaha bagi siswa SMK Farmasi. Pengabdian masyarakat bertujuan untuk meningkatkan pengetahuan dan wawasan siswa serta mendorong siswa  kelas XI dan XII SMK Farmasi Sekesal Surabaya dan SMK Farmasi Kapasari Surabaya untuk berwirausaha di bidang kosmetika. Metode pelaksanaan melalui webinar dengan  pemberian materi meliputi produk, formulasi, stabilitas dan perizinan produk kosmetika. Peserta mendapatkan kesempatan berdiskusi tentang materi yang diberikan,  mengerjakan pre/post test, mengisi evaluasi, dan membuat E-poster tentang produk kosmetika. Dari hasil evaluasi diketahui terdapat peningkatan pengetahuan dan wawasan peserta dan peserta tertarik untuk memproduksi sediaan kosmetika yang diharapkan dapat menjadi lahan usaha baru yang dapat meningkatkan kesejahteraannya.